1996
DOI: 10.1017/s0022112096001607
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of a gas cavity impacted by a weak or strong shock wave

Abstract: Two-dimensional simulations of gas cavity responses to both weak shocks (p ≤ 30 MPa) and strong shocks (p ranging from 500 to 2000 MPa) are performed using a finite volume method. An artificial viscosity to capture the shock and a simple, stable, and adaptive mesh generation technique have been developed for the computations. The details of the shock propagation, rarefaction, transmission and bubble wall motions are obtained from the numerical computations. A weak shock is defined in the present context as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
3
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 24 publications
(26 reference statements)
3
60
3
1
Order By: Relevance
“…As will be shown in this Letter, bubbles of the size of a few microns, even at moderate pressure amplitudes of 10 MPa, form a liquid jet in the direction of the propagating shock wave, which is in contrast to the findings of the numerical work of Ding and Gracewski [2]. There, shocks waves of 30 MPa did not cause jetting.…”
contrasting
confidence: 67%
“…As will be shown in this Letter, bubbles of the size of a few microns, even at moderate pressure amplitudes of 10 MPa, form a liquid jet in the direction of the propagating shock wave, which is in contrast to the findings of the numerical work of Ding and Gracewski [2]. There, shocks waves of 30 MPa did not cause jetting.…”
contrasting
confidence: 67%
“…Consequently, they operated on a time scale that was restricted to the early periods of the cavitation event, before these effects became important [43][44][45]. The advantage of the freeLagrange technique developed for this project [14,15,21] is that it can capture all these aspects, and follow the collapse through to the formation of the blast wave (which dominates the far-field emission from such a cavitation) and beyond.…”
Section: (B) the Kirchhoff Acoustic Emission Schemementioning
confidence: 99%
“…A typical simulation is shown in figure 7, where the shock wave is modelled as a travelling step pressure. In [41], the code was validated by comparing with the simulation results from previous papers [36,38]. It was found that the BEM code successfully captured the bubble deformation and collapse.…”
mentioning
confidence: 97%
“…Their results showed the reflection of shock waves inside the bubbles, and dynamic stress loading on nearby solid materials. In [37], the authors validated their code by comparing with an arbitrary Lagrangian Eulerian (ALE) simulation reported in Ding & Gracewski [38], who used the ALE method to solve the Euler equations for the simulation of a shock wave interaction with an air bubble. Both weak (less than 30 MPa in peak pressure) and strong (up to 2 GPa in peak pressure) shocks were investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation